Simulation of large-scale surges of the glacial Laurentide Ice Sheet : the simplified ISMIP HEINO experiments - GREVE, Ralf; TAKAHAMA, Ryoji
The 6th International Conference on Global Change : Connection to the Arctic (GCCA-6), 12–13 December 2005, Miraikan, Tokyo, Japan